A Case of Medically Rlefractory Epilepsy Treated with Vagal Nerve Stimulation: Initial Experience in Nepal - Gurung, Pritam; Shrestha, Resha; Dahal, Rizu; Lama, Manik Kumar; Dabadi, Sambardhan; Dhungel, Raju Raj; Pant, Basant (Annapurna Journal of Health Sciences, 2025)
Seizures are any sort of alteration in the brain’s electrical activity that is different from a normal signal and is usually characterized by abnormal body movement, loss of consciousness, frothing, and fainting. Usually, treatment of such conditions is carried out either with anti-epileptic drugs or surgical intervention. However, in some cases, both alternatives fail, and novel techniques of Vagus Nerve Stimulation (VNS) are necessary. In this case report we demonstrate a 24-year-old who had medically refractory seizure treated with VNS. The case was the first of its kind to be concluded in Nepal. This surgical technique is believed to explore a new dimension in the treatment of seizure patients in Nepal.